An Analysis of Client Performance in the Two-Chair Method - Sicoli, Lisa A.; Hallberg, Ernest T. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study investigates novice client performance using the Gestalt two-chair technique. Ten "softening" and eight "non-softening" counselling dyads were compared on performance task completion and sequentiality to investigate Greenberg's (1984) Refined Client Performance model of intrapsychic conflict resolution.